2014
DOI: 10.1186/1471-2164-15-s5-s1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of HIV drug resistance from genotype with encoded three-dimensional protein structure

Abstract: BackgroundDrug resistance has become a severe challenge for treatment of HIV infections. Mutations accumulate in the HIV genome and make certain drugs ineffective. Prediction of resistance from genotype data is a valuable guide in choice of drugs for effective therapy.ResultsIn order to improve the computational prediction of resistance from genotype data we have developed a unified encoding of the protein sequence and three-dimensional protein structure of the drug target for classification and regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 45 publications
(67 reference statements)
0
43
0
Order By: Relevance
“…Our previous work [7] showed that 5-fold cross validation was an appropriate statistical measure of quality for this dataset. All the sequences, including drug resistant and non-drug resistant mutants, were randomly assigned to one of five sets.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work [7] showed that 5-fold cross validation was an appropriate statistical measure of quality for this dataset. All the sequences, including drug resistant and non-drug resistant mutants, were randomly assigned to one of five sets.…”
Section: Methodsmentioning
confidence: 99%
“…This method accurately classified genotype data to predict drug resistance. In addition, it showed excellent correlation between predicted and observed levels of resistance in cross-validated regression analysis [19]. Mean shift clustering with regression analysis identified mutants, such as PR S17 , with high levels of resistance to multiple drugs that were representative of wide classes of drug-resistant proteins [20].…”
Section: Introductionmentioning
confidence: 99%
“…This second approach is also very popular and there exists machine learning software to predict resistance online [8, 9]. Different methods have been proposed, the most common ones being Linear Regression [10, 11], Artificial Neural Networks (ANN) [10, 1214], Support Vector Machines (SVMs) [10, 15, 16], Decision Trees (DT) [10, 17] and their ensemble counterpart, Random Forests (RF) [15, 16, 18, 19]. Some machine learning studies have complemented the sequence data with structural information, e.g., [11, 15, 16, 18], or have benefited from the knowledge about major drug associated mutations to perform feature selection.…”
Section: Introductionmentioning
confidence: 99%